Cultural Communication in Social Integration between Bawean Ethnic and Malay Sub-Ethnic in Malaysia - Sarifin, Muhammad Ridhwan (International Journal of Scientific Research and Management (IJSRM), 2020)
Cultural communication has obliquely shapes society relationships with another for the sake of togetherness prosperity. Diversity of norms and values from cultural symbols are able to be transferred as connecting elements in order to create interaction that is based on mutual comprehension of cultural norms. This study objective is to comprehend Bawean ethnic's cultural communication symbol. Employing qualitative methods, social construction paradigm is perceived through in-depth interview. This methodology adapted to realize the meaning of cultural communication between Bawaean and the other Malay sub-ethnicity. There are one main informant and ten other informant whom have been interviewed face-to-face. The result has shown that Bawean ethnic's cultural communication symbol such as language, cuisine, martial arts and religious rituals are the main elements in Bawean ethnic's cultural communication. In conclusion, cultural communication between Bawean ethnic and other ethnic has taken place according to the situations as either inside or outside  the group. Cultural similarities has facilitate cultural communication tranquility. It creates social integration with relation to the ethnic relationship processes such as acculturation, accommodation and integration.